Effect of Network's Morphology and Merge Bias Correction Procedures on Project Duration Mean and Variance - Giraldo González, Germán Eduardo; Opina Hernández, Gerardo; Roldán, Fabián (ELSEVIER, 2014)
Many authors have discussed the source of errors in PERT networks as follows: Uncertainty in the mean and variance calculations of (a) activity’s durations and (b) total project duration, and its related distributions. Different corrections formulas and procedures were proposed. In the other hand, there’s an existing risk of delay related to the project morphology, in terms of the number of activities, shape and complexity of the project network. However, the relationship of network’s morphology and the uncertainty of the whole project’s duration are poorly studied. In this research, a set of project networks with different morphology were generated and several methods available in literature (original PERT included) were used to estimate the parameters (mean and variance) of total project duration, then comparing them to the Monte Carlo Simulation as a representation of the reality, and the best and most accurate method(s) were chosen.

Muchos autores han discutido la fuente de errores en las redes PERT de la siguiente manera: Incertidumbre en la media y la varianza. cálculos de (a) duraciones de las actividades y (b) duración total del proyecto, y sus distribuciones relacionadas. Diferentes fórmulas de corrección y se propusieron procedimientos. Por otro lado, existe un riesgo de retraso relacionado con la morfología del proyecto, en términos de el número de actividades, la forma y la complejidad de la red del proyecto. Sin embargo, la relación entre la morfología de la red y La incertidumbre sobre la duración de todo el proyecto está poco estudiada. En esta investigación se utilizó un conjunto de redes de proyectos con diferentes Se generaron morfología y se utilizaron varios métodos disponibles en la literatura (incluido PERT original) para estimar la parámetros (media y varianza) de la duración total del proyecto, luego comparándolos con la simulación de Monte Carlo como un representación de la realidad y se eligieron los mejores y más precisos métodos.
Keywords: Knowledge management; Gestión del conocimiento; Research projects; Proyectos de investigación; Network analysis; Análisis de redes; Evaluation program and review technique; Programa de evaluación y técnica de revisión; Networks; Redes; PERT; Mean; Variance; Diferencia; Morphology; Morfología; Merge bias; Sesgo de fusión